EWASdb: epigenome-wide association study database. Issue Volume 47:Issue D1(2019) (13th October 2018) - liu, Di; Zhao, Linna; Wang, Zhaoyang; Zhou, Xu; Fan, Xiuzhao; Li, Yong; Xu, Jing; Hu, Simeng; Niu, Miaomiao; Song, Xiuling; Li, Ying; Zuo, Lijiao; et al.
Abstract: DNA methylation, the most intensively studied epigenetic modification, plays an important role in understanding the molecular basis of diseases. Furthermore, epigenome-wide association study (EWAS) provides a systematic approach to identify epigenetic variants underlying common diseases/phenotypes. However, there is no comprehensive database to archive the results of EWASs. To fill this gap, we developed the EWASdb, which is a part of 'The EWAS Project', to store the epigenetic association results of DNA methylation from EWASs. In its current version (v 1.0, up to July 2018), the EWASdb has curated 1319 EWASs associated with 302 diseases/phenotypes. There are three types of EWAS results curated in this database: (i) EWAS for single marker; (ii) EWAS for KEGG pathway and (iii) EWAS for GO (Gene Ontology) category. As the first comprehensive EWAS database, EWASdb has been searched or downloaded by researchers from 43 countries to date. We believe that EWASdb will become a valuable resource and significantly contribute to the epigenetic research of diseases/phenotypes and have potential clinical applications. EWASdb is freely available athttp://www.ewas.org.cn/ewasdb orhttp://www.bioapp.org/ewasdb .